The Effect of Situational Leadership and Compensation on Employee Performance Mediated by Career Development Opportunities at PT. CKD - Muhammad Tegar Wicaksana; Retno Purwani Setyaningrum (Majapahit Journal of Islamic Finance and Management, 2025)
In the era of globalization and increasingly competitive business competition, companies are required to have high-performance, adaptive, and professional human resources (HR). Employee performance is a key factor that determines the success of the organization, which is influenced by various variables such as leadership style and the compensation system implemented. However, the results of previous studies show inconsistencies regarding the influence of situational leadership and compensation on employee performance. Therefore, this study aims to analyze the influence of situational leadership and compensation on employee performance mediated by career development opportunities at PT. CKD. This study uses a quantitative method, sampling using the Lemeshow formula, and obtained a sample of 100 respondents. Data were collected through questionnaires distributed using Google Forms. Data management was carried out using Partial Least Squares (PLS) through the Structural Equation Model (SEM) technique with the help of the SmartPLS program version 4.1.1. The results of the analysis obtained show that situational leadership has a significant effect on employee performance at PT CKD. Compensation has a significant effect on employee performance at PT CKD. Career development opportunities have a significant effect on employee performance at PT CKD. Leadership significantly influences career development opportunities at PT CKD. Compensation does not significantly influence career development opportunities at PT CKD. Situational leadership has a significant influence on employee performance, with career development opportunities as a mediating variable at PT CKD. Compensation has a significant impact on employee performance, with career development opportunities as a mediating variable at PT CKD.